Perspectives of continuing education of teachers in environmental education: a study based on theses - Teixeira, Catarina; Marcelo de Carvalho, Luiz [UNESP] (Federal Univ Rio Grande, Inst Education, 2022)
This article aims to describe and understand the perspectives of continuing education addressed in theses on Environmental Education that focus their investigations on the processes of continuing education of teachers produced in Brazil. This research is part of the line of state-of-the-art investigations, having as a source the EArte Project database, where 36 theses were identified that focus on this theme. To analyze the works, we considered as a reference the perspectives of formation: technical, practical and critical. The analysis carried out allowed us to point out that in practically half of the theses analyzed it was not possible to identify the perspective that guided the development of the training process, as they were in a transition between technical, practical and critical perspectives, generating a certain incongruity in certain passages between these different perspectives. This panorama is an important direction for future research and/or practices of continued teacher education in the field of EE.
Keywords: Perspectives on teacher training; Continuing training; Environmental education